Peningkatan Nilai Overall Equipment Effectiveness Mesin Ball Mill Menggunakan Metode Total Productive Maintenance Di Pt Kohler Manufaktur Indonesia - Iqbal Fai Ramadhan; Hana Silvia Dwi Putri; Rini Siskayanti (Bajang Institute, 2026)
This study aims to analyze the Overall Equipment Effectiveness (OEE) of ball mills, identify the “six big losses,” and develop strategies to improve machine effectiveness through the implementation of the Total Productive Maintenance method at PT Kohler Manufaktur Indonesia. The study employs a quantitative approach, utilizing data on production, downtime, operating time, and product quality during the study period. The results show that the OEE value of the ball mill is still below world-class standards, indicating that there is still room for improvement in operational effectiveness. The dominant contributing factors stem from high breakdown losses and reduced operating speed, which lead to increased downtime and decreased machine productivity. TPM focuses on planned maintenance, autonomous maintenance, improving operator competence, establishing a schedule for periodic inspections, and standardizing maintenance procedures. The implementation of the proposed improvements is projected to increase the OEE value by improving availability, performance stability, and quality consistency, while simultaneously reducing the frequency of machine breakdowns and production downtime